2009
DOI: 10.1007/s12562-009-0168-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acid and alkaline pretreatment on the discoloration rates of dark muscle and myoglobin extract of skinned tilapia fillet during iced storage

Abstract: Discoloration profiles of dark muscle of skinned tilapia fillets were examined during iced storage after pretreatment with lactic acid (LA) or sodium carbonate (SC). During the subsequent storage, the a* values decreased gradually, and changed more rapidly when the pH was lower than 6.3. The fillet pretreated with 10% (v/v) LA exhibited the highest metmyoglobin formation ratio (MetMb%), followed by the fillet pretreated with 5% (v/v) LA, the control fillet, and the fillet pretreated with 10% (w/ v) SC. The sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 47 publications
0
16
0
2
Order By: Relevance
“…The cryoprotectant mixture used in this study, contains hydrogen peroxide as part of its formulation; however, L* was no improved; Himonides et al (1999) used hydrogen peroxide as a bleacher in cod mince and found no significant differences for "L" values. Chow et al (2009), concluded that the increase in L* could be caused by the alkaline pH of the cryoprotectant used. However, as described previously our results showed an increment in L* value due to the washing treatment.…”
Section: Physicochemicalmentioning
confidence: 99%
“…The cryoprotectant mixture used in this study, contains hydrogen peroxide as part of its formulation; however, L* was no improved; Himonides et al (1999) used hydrogen peroxide as a bleacher in cod mince and found no significant differences for "L" values. Chow et al (2009), concluded that the increase in L* could be caused by the alkaline pH of the cryoprotectant used. However, as described previously our results showed an increment in L* value due to the washing treatment.…”
Section: Physicochemicalmentioning
confidence: 99%
“…Mioglobin adalah protein globular yang mempunyai berat molekul berukuran kecil 17.000 kDa yang ditemukan pada daging (Chow et al 2009). Daging merah/gelap pada ikan tuna merupakan faktor penting dalam penentuan kualitas daging dan mempengaruhi faktor pembelian oleh konsumen.…”
Section: Pendahuluanunclassified
“…Analisis Mioglobin (Chow et al 2009) Sampel diblender hingga homogen, kemudian ditimbang sebanyak 1 g dalam tabung sentrifuse 50 mL dan ditambahkan 7 mL Aquabidest dingin, selanjutnya disentrifuse pada kecepatan 3000 G selama 15 menit. Sampel disaring dengan menggunakan kertas saring 0,2 µm.Sampel dipipet 1 mL, kemudian ditambahkan 0,5 mL pottasium buffer (25 µm pH 7) divortex, ditambahkan 25 µl larutan Na No 35%, divortex dan selanjutnya tambahkan 25 µl KCN 1%, divortex dan didiamkan selama 1 menit.…”
Section: Penyimpanan Bahan Bakuunclassified
“…The water-soluble fraction (prepared as described above) was used for the measurement of Mb extractability, as a parameter for the extent of Mb insolubilization (Chen and Chow 2001;Chow et al, 2009). To 1 mL of the extract was added 0.5 mL of 25 mM potassium buffer (pH 7.0) and gently mixed.…”
Section: Measurement Of Mb Extractabilitymentioning
confidence: 99%
“…Many attempts have been made to investigate the quality of fish and meat (Chow et al, 1985(Chow et al, , 2009Trout, 1989;Chen and Chow, 2001;Duran et al, 2008;Faustman, 2010; Determination of Mb derivatives The following procedures were carried out at 0 − 4℃ unless otherwise stated. The meat slice samples were homogenized with 7 volumes of ice cold water under moderate speed for 1 min using a homogenizer (Polytron model PT 10 − 35, Kinematica AG, Littau, Switzerland).…”
Section: Introductionmentioning
confidence: 99%